Pengaruh Penggunaan Model Pembelajaran Problem Based Instruction terhadap Kemampuan Pemecahan Masalah Matematis - Margana, Akhmad (Department of Mathematics Education Program IPI Garut, 2015)
Learning mathematics is meaningful when students can connect mathematical ideas, connecting mathematics to other disciplines, and connecting mathematics with everyday life, so that students can develop the skills. This quasi-experimental study aimed to determine. whether the mathematical problem-solving ability of students who get a Instruction problem based learning model better than students who received conventional learning models. The sample population in this study were 16 high school students Garut. These results indicate. that: ( 1 ) mathematical problem-solving ability of students who get a Instruction problem. based learning model better than students who received conventional learning models; ( 2 ) an increase in mathematical problem-solving ability of students who have learning model of Problem Based Instruction high category; ( 3 ) students' attitudes toward learning model of Problem Based Instruction in general showed a positive attitude.